Interactive Mode of Teaching Students in the Context of the Competence Paradigm - G. P. Sikorskaya; T. V. Savelyeva (Russian State Vocational Pedagogical University, 2015)
The paper explores the theoretical and practical aspects of interactive mode of teaching students by using active educational methods improving the quality of educational process and increasing students' motivation for comprehensive and in-depth learning. The list of interactive teaching techniques is given providing the development of necessary professional abilities and skills, and fostering students' responsibility for training results, critical thinking, reflexive skills, self-dependency in solving educational problems, training mobility, etc. The detailed descriptions of effective, yet comparatively new in subject-based teaching, methods of case studies and cross-cultural communication are provided, the opportunities for their implementation indicated. The paper emphasizes such aspects of educational process as self-assessment and peer-assessment of students' achievements. The authors suggest the original approach to educational results evaluation in interactive educational environment, shifting the emphasis from students' lack of knowledge and skills onto their abilities and achievements. The exact criteria of current control help optimize students' extracurricular self-dependent work, providing teaches with the feasible leverages for controlling this important activity significantly enlarged in proportion in modern education. As the final control, the authors have chosen defending the thematic portfolio in electronic form, which allows integrating qualitative and behavioral assessment of the assimilated training course. The present research was carried out in the context of the competence paradigm of education. The paper contains the research findings in the field of comparative pedagogy and demonstrates the experience of implementing the interactive teaching mode exemplified by «Sustainability and the Environment» virtual course for bachelors and master's degree holders training in the humanities and natural sciences profiles.